Age and gender as factors in visual photographic memory - Khanam, Mahfuza (Dhaka University Journal of Biological Sciences, 2022)
Exploring the role of gender and age in visual photographic memory were the objectives of the present study. A sample of 60 boys and 60 girls, aged between 11 to 16 years, participated in the current study. Results indicated that boys outperformed girls in visual photographic memory task. Age also found to be a significant variable. Significant mean differences have been observed among the respondents of 13, 14, 15, and 16 year with 11 year; 12 with 16; 13, 14, 15 with only 11 and finally 16 with age 11 and 12. Results revealed that there exists a significant mean difference between age 11 and 16. Findings also showed that visual memory increases with increasing age. But the rate of development is not same through all the years. Dhaka Univ. J. Biol. Sci. 30(3 CSI): 385-392, 2022 (June)